Analysis on Fracture Failure of High - Strength Bolt - ZHANG Li - feng, TONG Hai - sheng, WANG Wei - dong, LIU Ke - hong, LI Hai - jie, WANG Zhi - qiang, WEN Gang - zhu, WANG Ya - jun, TANG Xi - rong (Cailiao Baohu, 2021)
After the assembling, the fracture occurred on the high - strength bolt M8×1 mm - 25 mm with the material of PCrMo steel. By the means of macroscopic, metallographic microscope and scanning electron microscope (SEM), reasons for the fracture failure of the high - strength bolt were analyzed from the perspectives of microstructure and fracture morphology. Result showed the chemical elements and the hardness of the bolt met the design requirement specified in drawing. However, during the assembling, the installation method and torque of the bolt were failed to be specified, so that the bolt was received much external force, it was showed the fracture and core displayed intergranular cracking and dimple morphology. And the technological process of the bolt surface was further analyzed, it showed that pickling process before phosphating and phosphating process led to the increase of hydrogen content in the substrate. So the bolt was fractured finally by the combined action of the abnormal external force and hydrogen embrittleness of substrate. For the above fracture causes, when the technological measures including the designated fixing torque, special toolings for assembly and the optimum process of the surface treatment were adopted, the fracture of the bolt was resolved.